Effect of cognitive behaviour therapy programme in enhancing health seeking and health information utilization of undergraduates living with sickle cell trait in Ogun state, Nigeria - Ayodele, Kolawole Olanrewaju; Morka, Emmanuel Onyesi; Ossai-Opute, Chinedu Sandra; Ademuyiwa, Motunrayo A.; Olurinola, Eunice Funmilayo (Edelweiss Applied Science and Technology, 2025)
This study assessed the impact of cognitive-behavioral therapy (CBT) on health information seeking and utilization among undergraduates living with sickle cell traits in Ogun State, Nigeria. The research adopted a quasi-experimental design. The population consisted of 23 undergraduate students living with sickle cell disease. Participants were exposed to CBT. The reliability of the questionnaire was confirmed using Cronbach’s alpha coefficient, which ranged from 0.78 to 0.81. Data collected before and after the intervention were analyzed using descriptive and inferential statistics at a 0.05 significance level. Results showed significant differences in participants' knowledge of sickle cell disease (t(21) = 10.587, p = .011 < .05), health-seeking behavior (t(21) = 8.881, p = .000 < .05), and health information utilization (t(21) = 15.321, p = .000 < .05) after exposure to CBT. Additionally, a significant difference was observed between the mean scores of participants on health information utilization at P1 and P2 (t(21) = 3.654, p = .000 < .05). It was concluded that integrating CBT components into healthcare can promote positive thoughts and improve healthy lifestyles.